Development of a uroflowmeter - Teh, Zhen Ping. (2013)
Benign prostatic hyperplasia(BPH) is a voiding dysfunction that affects more than half of men by the age of 50. The uroflowmetry test provides quantitative information such as the flow rate, the total volume of urine expelled by the body and the voiding time of the urine. The majority of existing clinical uroflowmeters which are found in specialist clinics are expensive and require an operator in the clinic to serve the patient which makes it difficult for patients who want to receive testing at home. Thus, the goal of this final year project is to develop an affordable and user friendly uroflowmeter to increase productivity of the clinic and provide valuable medical information on the condition of the patient at home.